Local influence of floral resource attributes on urban bumble bee foraging activity - Pfeiffer, Vera W.; Zhu, Jun; Poh, Karen; Silbernagel, Janet (Frontiers in Sustainable Cities, 2023)
Urbanization diminishes the extent of uncompacted, exposed soil and the coverage of wild plant species, yet still supports diverse pollinator communities when their habitat is maintained within the built environment. Floral abundance and richness are known to influence bee foraging behavior, and these factors vary across the landscape, especially across heterogeneous urban extents. This study assesses how floral resources are distributed across the city of Madison, WI and how these factors influence the distribution of foraging bumble bees. We conducted a systematic walking transect survey of bumble bees across Madison, WI. The resulting point location data associated with more than 5,000 non-lethally surveyed bumble bees were analyzed with regard to floral resource explanatory variables as well as underlying land use zoning on more than 700 transects. We used Moran's I correlograms to investigate spatial autocorrelation in floral resource variables and bumble bee counts, then we fitted a generalized linear model predicting transect bee counts based on floral cover, density, species richness and wild plant species richness on the distribution of foraging bees, and found significant positive influence of flower cover, species richness, and weakly significant positive influence of wildflower species richness on foraging bee counts within the model as well as a significant positive influence of the land use zoning categorical variable. We employed a geographically-weighted regression model to explore non-stationarity in the effects of floral resource explanatory variables across the study extent, to suggest that the effects of floral resource predictors on foraging bumble bee behavior may vary based on landscape context across the city. The results of this study show that landscapes with high cover as well as floral diversity maximize bumble bee foraging, and the positive effect of wildflower species richness stands out where floral cover and overall richness are also present. Given that urban landscapes are not homogeneous and that floral resources are not consistently distributed across the cityscape, valuable pollinator habitat should be protected, and supplemented where gaps persist.